STRATEGI PUBLIC RELATIONS FAVEHOTEL MANAHAN SOLO DALAM UPAYA MENINGKATKAN REPUTASI HOTEL - Nugraheni, Monica Windrastuti Dyah; Sarjono, Herning Suryo; Itasari, Andri Astuti (Solidaritas, 2024)
This research aims to describe the Public Relations strategy of Favehotel Manahan Solo in an effort to improve the hotel's reputation. This research uses descriptive type qualitative research. The method used is a case study. This research data collection technique uses primary data obtained through interviews and observation, as well as used secondary data both through documentation and from references such as books and journals. The validation technique used is triangulation. Based on the results that the strategy implemented by Public Relations of favehotel Manahan Solo yaitu with conducting in-depth research first, after obtaining data from the field, programs are prepared or planned that are appropriate to the existing situation, then action and realization involving various parties in carrying out each program that has been planned, as well as evaluation as the final stage which aims to be a form of evaluation of work and also existing facilities so that they can be improved in the future so as to increase the reputation of the hotel. Forms of program results include social media branding, advertorials, reply to all guest comments, collabs and partnerships, CSR, media relations, joining events, and press releases.